Analysis of Environmental and Social Scores on Firm Profitability, Lending and Dividends in Germany and the UK - Fatmy, Veda (My University, 2016)
This paper aims to investigate the effects of separate components of corporate social responsibility—social and environmental efforts in particular—on a firm’s operating profit margin, dividends per share and net debt. It also investigates whether such efforts can reduce firm exposure to market risk. One or a combination of these factors may consequently be responsible for lower expected returns on firms with greater ES ratings. For this purpose we study firms on the FTSE-100 and the HDAX from the period 2002-2014. Environmental and social scores for these firms are regressed against operating profit margin, dividends per share and net debt while controlling for relevant factors. The firms are then divided into groups based on their environmental and social rankings and we compare the covariance of their returns with market returns to gauge the relation of their sensitivity (beta) to ES scores. The results of the first part of the study indicate that ES scores are more strongly correlated with OPM, Div/Share and Net debt in HDAX than in FTSE-100. In addition there is a slight positive correlation between firm beta and ES scores, implying increased exposure to market risk.
Keywords: Corporate Social Responsibility; Environmental scores; Social scores; Operating Profits Margin; Dividends per share; Net Debt; exposure to market risk; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|